Partisipasi Masyarakat dalam Musyawarah Perencanaan Pembangunan di Kelurahan Palangka Kota Palangka Raya: Community Participation in Development Planning Deliberations in Palangka Village, Palangka Raya City - Masrukin, Masrukin; Anwar, Anwar (Pencerah Publik, 2017)
This study aims to find out, explain and describe community participation in development planning meetings in Palangka Kelurahan, Palangka Raya City. This study uses qualitative research methods, the research conducted is a descriptive study where community participation in development planning in Palangka Kelurahan Palangka Raya City was chosen as the location of the study. Techniques for collecting data by observation, interviews, and documentation. Based on the results of the study it can be concluded that the development system in the Palangka Village is a political process to obtain joint opportunities through activities in which there are negotiations between all development actors. The development system in the Palangka village is carried out transparently so that the community has the convenience and knowledge of each development process and every stage of its development. In this case, it is more a tool for decision makers who are expected to be able to find out what the community needs.